PELATIHAN PENYAJIAN LAPORAN POSISI KEUANGAN UNTUK PERUSAHAAN JASA DAN DAGANG PADA SISWA SMA ST. TARSISIUS - Ferry Adang; Hannah Lowena; Riyanti Teresa; Tannia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
The presentation of financial statements is essential for companies in carrying out their activities which require functions to play a role in processing transactions, capturing and compiling economic events that occur and then documenting them in the form of financial statements according to applicable Financial Accounting Standards. Accounting knowledge is important for high school students in preparation for higher education. This activity is a Pengabdian Kepada Masyarakat (PKM) that provides benefits in the form of basic knowledge and skills about accounting, especially the presentation of financial position reports of trading and service companies provided to Tarsisius 1 High School students located in the Hasyim Ashari area, Central Jakarta. The form of activities is in the form of theoretical exposure, discussion of case questions as a simulation of the accounting process, and offline interactive discussions to help schools improve literacy in understanding the basics of accounting for St. Tarsisius 1 High School students. St. Tarsisius I High School needs additional basic accounting knowledge to foster interest in continuing education to a higher level. Therefore, the PKM Untar Team proposed basic accounting themed training as an extracurricular activity for classes X - XII. This activity is planned for Wednesday, October 29, 2025 offline at the school, including material presentation, discussion of sample problem simulations, and question and answer sessions. The output of this activity is mandatory output in the form of proceedings or journals that will be included in seminars organized by Untar, as well as additional output in the form of potential Intellectual Property Rights (IPR) Copyright. Penyajian laporan keuangan merupakan hal esensial bagi perusahaan dalam menjalankan aktivitasnya yang memerlukan fungsi untuk berperan dalam memproses transaksi, menangkap dan menyusun peristiwa ekonomi yang terjadi kemudian mendokumentasikannya dalam bentuk laporan keuangan sesuai Standar Akuntansi Keuangan yang berlaku. Pengetahuan akuntansi penting bagi siswa SMA sebagai persiapan menempuh pendidikan tinggi. Kegiatan ini merupakan Pengabdian Kepada Masyarakat (PKM) yang memberikan manfaat berupa pengetahuan dan keahlian dasar tentang akuntansi, khususnya penyajian laporan posisi keuangan perusahaan dagang dan jasa yang diberikan kepada siswa SMA Tarsisius 1 yang berlokasi di daerah Hasyim Ashari, Jakarta Pusat. Bentuk kegiatan berupa pemaparan teori, pembahasan soal kasus sebagai simulasi proses akuntansi, serta diskusi interaktif secara luring untuk membantu sekolah meningkatkan literasi pemahaman dasar-dasar akuntansi bagi siswa SMA St. Tarsisius 1. SMA St. Tarsisius I membutuhkan tambahan pengetahuan akuntansi dasar guna menumbuhkan minat melanjutkan pendidikan ke jenjang lebih tinggi. Oleh karena itu, Tim PKM Untar mengusulkan pelatihan bertema akuntansi dasar sebagai kegiatan ekstrakurikuler kelas X - XII. Kegiatan ini direncanakan pada Rabu, 29 Oktober 2025 secara luring di sekolah, meliputi pemaparan materi, pembahasan simulasi contoh soal, dan sesi tanya jawab. Luaran kegiatan ini adalah luaran wajib berupa prosiding atau jurnal yang akan diikutsertakan dalam seminar yang diselenggarakan oleh Untar, serta luaran tambahan berupa Potensi Hak kekayaan Intelektual (HKI) Hak Cipta.